Mejoramiento de la difusión de la información turística de la región San Martín mediante el uso del e-marketing - Pinedo García, Gisella (2014)
E-Marketing as a diffusion tool of touristic information about San Martin region, focuses on the problem of poor touristic diffusion of San Martin region agents and tour operators have to competition and not having a solid and reliable presence on the internet to spread the updated product, services information about the region. The E-Marketing (set of strategies, techniques and operations coordinated through the internet, looking to increase sales of their products) was used, in this research as a strategic tool to improve the touristic information about San Martin region. Population used for this research were national and foreign tourists visiting Tarapoto city, a part of this tourist were taken as a sample, first pre-survey was conducted after spread information traditionally, then a post-survey was conducted to spread information after the stimulus variable “Use of E-Marketing”, by web page implementation in a CMS platform. This was done in order to assess the quality of the tourist information is spreading, these data were then used for hypothesis testing, which showed that the use of E-Marketing generates better spread of tourist information of the region of San Martin.